To Study the Combined Use of Pleural Fluid Lymphocyte / Neutrophil Ratio and ADA for the Diagnosis of Tuberculous Pleural Effusion - Dr. Pamarthi Nagarjuna,; Dr. N Madhusudan Babu,; Dr. K Sudheer, (International Journal of Scientific Research in Science and Technology, 2024)
INTRODUCTION - Pleural effusion is the abnormal collection of fluid in the pleural space. It is classified into exudates and transudates based on Light's criteria. Among the extra pulmonary presentations after tuberculous lymphadenitis, pleural TB is the second frequent. Although many biochemical parameters, such as lactate dehydrogenase (LDH), C-reactive protein (CRP), adenosine deaminase (ADA), interferon-gamma, and procalcitonin levels have been studied in the context of the diagnosis of exudative pleural effusion, its diagnosis is still challenging.AIMS & OBJECTIVES- To determine whether the combined use of ADA activity and lymphocyte/neutrophil ratio would provide a more efficient means for diagnosing tuberculous pleural effusion than the use of ADA alone.MATERIAL & METHODS- Hospital based Observational study was conducted over 8 months with total number of 100 Patients diagnosed as having pleural effusion based on clinical features and chest radiography in GEMS MEDICAL COLLEGE AND HOSPITAL. Biochemical, cytological and microbiology studies were done by obtaining pleural fluid by thoracocentesis.RESULTS - out of 100 cases, 84 cases were tubercular and had high level of ADA in comparison to rest of 16 non tubercular cases. At level of 50 IU/L of ADA activity test had sensitivity of 97.6%, specificity 87.5% which was increased to 100% and 92.8% in combination with test of Lymphocytic/Neutrophilic ratio - 0.75CONCLUSION- The combined use of ADA along with the L/N ratio would provide a more efficient means for diagnosing tuberculous pleural effusion than the use of ADA alone.
Keywords: Pleural Effusion; Lymphocyte; Adenosine Deaminase; Neutrophil Ratio